Size‐Dependent Thermochromism through Enhanced Electron–Phonon Coupling in 1 nm Quantum Dots1. Issue 40 (11th August 2014) - Tamaki, Haruna; Watanabe, Hiroto; Kamiyama, Sachiko; Oaki, Yuya; Imai, Hiroaki
Abstract 1 nm CuO quantum dots (QDs) were produced in size‐controlled super‐micropores of a silica matrix. The reversible color change of the QDs from pale blue to deep green was clearly observed in a wide temperature range from 298 to 673 K. This particular thermochromism is ascribed to an enhanced bandgap shift depending on temperature with a strong electron–phonon coupling in the confined space of the 1 nm QDs.